‘Close to the bone’? Catalysts for integrating HIV and AIDS into the academic curriculum - de Lange, Naydene; van Laren, Linda; Tanga, Pius (South African Journal of Higher Education, 2018)
Integrating HIV and AIDS into the academic curriculum remains a challenge which, for various reasons, is not fully taken up by academics at universities. Although much is being done in the health arena, and education is often put forward as the ‘antidote’ for the epidemic, only a few academics have introduced HIV and AIDS into the curriculum. In this article we explore why some academics integrate HIV and AIDS into their curricula, what the catalyst was for doing so and how these academics see their integration. The qualitative study, within an interpretivist framework, consisted of a multiple case study, using individual interviews as well as drawings, to elicit responses from the purposively selected academics. The themes that emerged are: ‘It’s here, it’s not somewhere out there’; ‘People matter’; ‘Buying into the idea’; and ‘It’s a directive’. The findings lead us to conclude, using a theory of social proximity as lens, that the vigour of integrating HIV and AIDS is linked to how ‘close to the bone’ the pandemic is experienced, not only at personal but also at community level. This clearly has implications for working with academics to integrate HIV and AIDS into the curriculum.